2010
DOI: 10.1002/biot.200900197
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylglycerol and glucosylglycerate as enzyme stabilizers

Abstract: Compatible solutes constitute a diverse class of low-molecular-mass organic molecules that are accumulated in high intracellular concentrations in response to the external stress of hyperosmolality or high temperature. Many of these compounds like alpha, alpha-trehalose are well known for their stabilizing effect on protein structure and could lead to development of more stable protein formulations. Negatively charged solutes like mannosylglycerate (R-2-O-alpha-D-mannopyranosyl-glycerate) are widespread among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…We preliminarily confirmed that sorbitol, a practical agent for protecting of protein that is used in the food industry at 4-5%, 29) inhibited heat aggregation of egg white at a concentration of 5% (275 mM), whereas 5% GGA-Na (170 mM) had a stronger inhibitory effect on the heat aggregation of egg white than that of 5% sorbitol's (data not shown). The GA structure may therefore contribute a protein-protective property of GGA as an enzyme stabilizer, 30) and GA itself represents a superior protein-protective agent. Such activity will play an important role in vivo, such as protecting biological molecules during adaptation to environmental changes.…”
mentioning
confidence: 99%
“…We preliminarily confirmed that sorbitol, a practical agent for protecting of protein that is used in the food industry at 4-5%, 29) inhibited heat aggregation of egg white at a concentration of 5% (275 mM), whereas 5% GGA-Na (170 mM) had a stronger inhibitory effect on the heat aggregation of egg white than that of 5% sorbitol's (data not shown). The GA structure may therefore contribute a protein-protective property of GGA as an enzyme stabilizer, 30) and GA itself represents a superior protein-protective agent. Such activity will play an important role in vivo, such as protecting biological molecules during adaptation to environmental changes.…”
mentioning
confidence: 99%
“…GGP shows sequence identities of 28.3 (234/828) and 31.9% (257/805) to LbMP and CsKP, respectively. The GH65 enzymes consist of four distinct regions: an N-terminal ␤ sandwich domain (residues 1-250 in GGP, blue), a linker region (251-286, cyan), a catalytic (␣/␣) 6 barrel domain (290 -687, yellow), and a C-terminal domain (287-289 and 688 -761, red). GGP forms a dimer in solution (11).…”
Section: Resultsmentioning
confidence: 99%
“…Protein Expression and Purification-The expression vectors for C terminally (His) 6 -tagged wild-type GGP and its E475Q mutant (11) were introduced into Escherichia coli BL21 CodonPlus (DE3)-RIL (Stratagene, La Jolla, CA). The transformants were cultured in Luria-Bertani medium containing 50 mg/liter of kanamycin and 100 mg/liter of chloramphenicol at 37°C for 4 h. Isopropyl 1-thio-␤-D-galactopyranoside was added to a final concentration of 0.1 mM to induce protein expression.…”
Section: Methodsmentioning
confidence: 99%
“…Such transgenic crop plants may show sustainable growth under saline or drought conditions. Moreover, significant GG accumulation in potato tubers could be used as raw material for GG purification, which is used under the trade name glycoin in cosmetics or pharmaceuticals as moisture or stabilizer (http://www.bitop.de; [31]). …”
Section: Introductionmentioning
confidence: 99%
“…GG is effective to protect macromolecules against denaturation has been proven with many in vitro systems [28,29,31]. The improved fitness of salt and drought-stressed transgenic potato plants can also be related to the overall increase of soluble sugars inside leaves.…”
mentioning
confidence: 99%